Influence of Titration of Neurohormonal Antagonists and Blood Pressure Reduction on Renal Function and Decongestion in Decompensated Heart Failure. (January 2016) - Kula, Alexander J.; Hanberg, Jennifer S.; Wilson, F. Perry; Brisco, Meredith A.; Bellumkonda, Lavanya; Jacoby, Daniel; Coca, Steven G.; Parikh, Chirag R.; Tang, W.H. Wilson; Testani, Jeffrey M.
Abstract : Background—: Reduction in systolic blood pressure (SBP reduction) during the treatment of acute decompensated heart failure is strongly and independently associated with worsening renal function. Our objective was to determine whether SBP reduction or titration of oral neurohormonal antagonists during acute decompensated heart failure treatment negatively influences diuresis and decongestion. Methods and Results—: SBP reduction was evaluated from admission to discharge in consecutive acute decompensated heart failure admissions (n=656). Diuresis and decongestion were examined across a range of parameters, such as diuretic efficiency, fluid output, hemoconcentration, and diuretic dose. The average reduction in SBP was 14.4±19.4 mm Hg, and 77.6% of the population had discharge SBP lower than admission. SBP reduction was strongly associated with worsening renal function (odds ratio, 1.9; 95% confidence interval, 1.2–2.9; P =0.004), a finding that persisted after adjusting for parameters of diuresis and decongestion (odds ratio, 2.0; 95% confidence interval, 1.3–3.2; P =0.002). However, SBP reduction did not negatively affect diuresis or decongestion ( P ≥0.25 for all parameters). Uptitration of neurohormonal antagonists occurred in >50% of admissions and was associated with a modest additional reduction in blood pressure (⩽5.6 mm Hg). Notably, worsening renal function was not increased, and diuretic efficiency was significantly improved with the uptitration of neurohormonal antagonists. Conclusions—: Despite a higher rate of worsening renal function, blood pressure reduction was not associated with worsening of diuresis or decongestion. Furthermore, titration of oral neurohormonal antagonists was actually associated with improved diuresis in this cohort. These results provide reassurance that the guideline-recommended titration of chronic oral medication during acute decompensated heart failure hospitalization may not be antagonistic to the short-term goal of decongestion. Abstract : Supplemental Digital Content is available in the text.